Penerapan Model Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Hasil Belajar - Rizki Kurniawan; Uus Manzilatusifa; Bella Anantha Sritumini (EDUCARE, 2013)
This research is motivated by the low learning outcomes of students in economic subjects. In learning activities students are expected to interact actively with teachers, students with students, and students with the environment, so that learning activities can run well in hopes of improving learning outcomes. Learning Outcomes of students will increase if the learning creates good interactions. Therefore learning methods are used which require interaction in learning by applying the STAD Cooperative Learning Model type. The research method used is the experimental method, while the nature of the research used in this study is quantitative research. The results of the study show that: (1) The results of processing observational data can be seen that the STAD Cooperative Learning Model can be applied in economic learning; (2) There are differences in the improvement of student learning outcomes in the experimental class and the control class; (3) Application of the STAD Cooperative Learning Model can improve learning outcomes. The results showed a comparison of the increase in the pretest and posttest values in the gain test. Thus it can be concluded that the application of the STAD type cooperative learning model can improve learning outcomes.